2019
DOI: 10.1039/c8nj03907k
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide (NO) photo-release in a series of ruthenium–nitrosyl complexes: new experimental insights in the search for a comprehensive mechanism

Abstract: The mechanism of nitric oxide release is investigated along a series of 1–3 “push–pull” ruthenium nitrosyl complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…1 H-NMR appears to be an excellent tool for defining the coordination sphere of [Ru(tpy)(bpy)X] species. We have previously reported that the chemical shift of the proton in position 6 on the bipyridine, is very sensitive to the nature of the X ligand attached to the ruthenium center, due to the spatial proximity between H-6 and X and the subsequent different electronic environment ( Figure 1 ) [ 23 , 24 ]. Three different compounds (A, B, C) are observed on the spectra, with various concentrations throughout the irradiation process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 H-NMR appears to be an excellent tool for defining the coordination sphere of [Ru(tpy)(bpy)X] species. We have previously reported that the chemical shift of the proton in position 6 on the bipyridine, is very sensitive to the nature of the X ligand attached to the ruthenium center, due to the spatial proximity between H-6 and X and the subsequent different electronic environment ( Figure 1 ) [ 23 , 24 ]. Three different compounds (A, B, C) are observed on the spectra, with various concentrations throughout the irradiation process.…”
Section: Resultsmentioning
confidence: 99%
“…The examination of Figure 2 reveals that the starting compound (A) is gradually transformed to the final product (C), B appearing as a possible intermediate in a global photoreaction which, at first, can tentatively be written as A → B → C. This assumption has to be considered in the context of previous investigations conducted in acetonitrile, in which the irradiation of [RuT1B0(NO)](PF 6 ) 3 leads to the complete release of NO·, [RuT1B0(MeCN)](PF 6 ) 2 being clearly identified as the final photoproduct (Reaction (1)) [ 23 , 24 ]. Importantly, no additional or intermediate species is observed in acetonitrile, in striking contrast with the present investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ruthenium nitrosyl complexes have attracted considerable interest over the last decades because of their multifunctional photoresponsive capability. Indeed, these complexes can display photochromism in the solid state [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and be efficient agents for NO photorelease in solution [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Despite the numerous studies exploiting these two distinct photoreactivities (i.e., N→O linkage photoisomerization and photoinduced NO delivery), the underlying mechanisms are notoriously complex to unravel based on the available experimental observations [12,30].…”
Section: Introductionmentioning
confidence: 99%